2019
DOI: 10.1186/s42269-019-0096-8
|View full text |Cite
|
Sign up to set email alerts
|

Processed cocoa pod husk dietary inclusion: effects on the performance, carcass, haematogram, biochemical indices, antioxidant enzyme and histology of the liver and kidney in broiler chicken

Abstract: Background: In a 42-day feeding trial, the effects of processed cocoa pod husk (PCHM) inclusion in a broiler chicken diet were assessed. Methods: This experiment was conducted between December 2017 and January 2018. Cocoa pod husk was collected and processed by ash treatment and rumen liquor fermentation to form a processed cocoa pod husk (PCHM). Three experimental diets were formulated at both the starter and finisher phases, in which PCHM was included at 0, 4 and 8% and designated as diets 1, 2 and 3, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
10
0
2
Order By: Relevance
“…The Moringa seed offers concentrated nutrients including amino acids, proteins, and a wide range of vitamins and minerals, making it an outstanding supplement for stressed and hurried individuals and a solid source of nutrition for undernourished populations around the World (Peter & Philip, 2014). Furthermore, the fonio-moringa seed meal (FMSM) could be classified as phytogens (Abd El-Hack et al, 2018) and generally, phytogenic feed supplements or additives are reported to have influence on the heamatological and serum biochemical indices (Oloruntola, Agbede, Ayodele, & Oloruntola, 2018) and histology and morphology of internal organs of the animals (Adeyeye, Ayodele, Oloruntola, & Agbede, 2019;Oloruntola, 2018).…”
mentioning
confidence: 99%
“…The Moringa seed offers concentrated nutrients including amino acids, proteins, and a wide range of vitamins and minerals, making it an outstanding supplement for stressed and hurried individuals and a solid source of nutrition for undernourished populations around the World (Peter & Philip, 2014). Furthermore, the fonio-moringa seed meal (FMSM) could be classified as phytogens (Abd El-Hack et al, 2018) and generally, phytogenic feed supplements or additives are reported to have influence on the heamatological and serum biochemical indices (Oloruntola, Agbede, Ayodele, & Oloruntola, 2018) and histology and morphology of internal organs of the animals (Adeyeye, Ayodele, Oloruntola, & Agbede, 2019;Oloruntola, 2018).…”
mentioning
confidence: 99%
“…Cocoa pod husk is also utilized as cattle fodder. It aims to reduce conventional corn and bran-based feed while also lowering the feed cost [29]. Research is still needed to ascertain its effect on the digestive system of animals.…”
Section: Animal Feedmentioning
confidence: 99%
“…Mainly, kola nut husk, cattle and poultry wastes, among others, are essential components of agro wastes. If not adequately disposed of or utilised for productive purposes, it could constitute a nuisance to the environment [2,3,4].…”
Section: Introductionmentioning
confidence: 99%